Merancang Evaluasi Program Pendidikan - Rosita; Zurqoni; Sugeng (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
Evaluation in education programs serves as a tool to monitor and assess the outcomes of existing program efforts. However, a thorough planning is necessary in evaluating such programs. This study employs a literature review approach where relevant literature is selected based on the topic under discussion. The aim is to gather information regarding the design of educational program evaluation. The analysis results indicate that: (1) the involvement of key individuals is crucial in designing educational program evaluations, namely sponsors, evaluator, clients, participants, stakeholders and audiences, (2) there are five steps in the process of designing educational program evaluations: (a) assessing the context, conducted by the evaluator, (b) collecting observation results, carried out by the evaluator with assistance from stakeholders, (c) involving stakeholders who possess knowledge and play significant roles from the initial stage throughout the evaluation process, (d) outlining the program, where the evaluator conducts a comprehensive review of program documents and relevant sources after interacting with stakeholders, (e) focusing the evaluation, where the evaluator needs to collaborate with the sponsor to prioritize needs to be addressed in the evaluation plan, (3) five steps in designing educational program evaluations (Dina P, et al., 2019): (a) assessing the context, conducted by the evaluator by seeking opinions/views from organizational colleagues or guardians, (b) collecting observation results, by examining, understanding, and investigating the reasons for conducting the program evaluation, (c) involving stakeholders, with the aim of ensuring that the program evaluation is contextually appropriate and aiding in fostering cooperation during the evaluation process, (d) outlining the program, to provide insights, help determine design, and uncover intangible aspects, (e) focusing the evaluation, detailing concrete plans and operationalizing questions to be asked and steps to be taken, as well as assigning tasks to be performed by program evaluation staff.